SHOPPING MALL LIBRARY: KAJIAN TERKINI DI EMPAT NEGARA ASIA TENGGARA - Sulaiman, Madiareni (BACA: Jurnal Dokumentasi dan Informasi, 2016)
This paper discuss about recent researches with shopping-mall library as the main topic and their management for society. This concept is unique because we view the library as a place for user. It is actually already a familiar thing for user in developed country, like United States, United Kingdom and Australia. But, in some of the Southeast Asian country, it is already applied for the last ten years, especially Indonesia. However, it has slow response in Indonesia because the lack of socialization.Whereas, in the other Southeast Asian country, this kind of library was full supported by government and private company.This paper uses qualitative research with literature study from books, journal articles and web articles. It is delivered with systematic description of recent studies. The study is limited to the Southeast Asia region, especially in Singapore, Malaysia, Thailand and Indonesia. The result of study is that shopping-mall library already applied in some country with different terms, such as Library@Mall in Singapore, myLibrary in Malaysia, Knowledge Park in Thailand and TBM@Mall in Indonesia. It is managed by government and private institution in order to make sustainable development for library management (vision, resources: staffs, collections and facility, and socialization/promotion).